Design, síntese e caracterização de hidrogéis e nanocompósitos de carboximetil celulose com incorporação de nanopartículas de prata e fármaco doxorrubicina para potencial aplicação na regeneração epitelial antibacteriana e antitumoral frente à linhagem celular de melanoma humano : estudos in vitro de atividade antibacteriana e antitumoral frente à linhagem celular de melanoma humano - Nádia Sueli Vieira Capanema (2018)
This study focused on the design, synthesis and comprehensive characterization of environmentally friendly hydrogel membranes based on carboxymethyl cellulose (CMC) for wound dressing and skin repair substitutes. These new CMC hydrogels were prepared with two degrees of functionalization (DS = 0.77 and 1.22) and chemically crosslinked with citric acid (CA) for tuning their properties. Additionally, CMC-based hybrids were obtained by blending with polyethylene glycol (PEG) and nanocomposites with antibacterial and antitumor properties were synthesized combining CMC and silver nanoparticles (AgNPs) and by conjugation of doxorubicin (DOX) with CMC polymer, respectively. The results demonstrated that superabsorbent hydrogels (SAP) were produced which was significantly dependent on the concentration CA crosslinker, the DS of CMC, the addition of PEG as network modifier, the presence of AgNPs and DOX chemotherapeutic. The spectroscopical characterizations indicated that the mechanism of CA crosslinking was mostly associated with the chemical reaction with CMC hydroxyl groups and the CMC-based hydrogels (CMC, CMC-PEG and CMC-AgNPs) were cytocompatible considering the in vitro cell viability responses. In addition, PEG played an important role on the formation of a hybrid polymeric network with very distinct morphological and nanomechanical features. CMC–AgNP nanohybrids demonstrated highly effective antibacterial activity against gram-positive multi-resistant wound/skin pathogens (Staphylococcus aureus) and moderate effect towards gramnegative strains (Escherichia coli and Pseudomonas aeruginosa). The carbohydrate-based prodrug composed of CMC bioconjugated with DOX by covalent amide bonds demonstrated the effect of CMC hydrogel network structure with distinct degree of substitution regarding to the process of bioconjugation and on tailoring the DOX release kinetics in vitro and the cytotoxicity towards melanoma cancer cells in vitro. Therefore, SAP hydrogels were designed and produced with properties that are tunable through the extension of crosslinking and degree of substitution of carboxymethyl groups of the cellulose backbone. To this end, they are envisioned as promising hydrogels with key properties for assisting skin wound healing and regeneration, offering promising perspectives for skin disease applications associated with antibacterial activity and topical chemotherapy of melanoma.